2016
DOI: 10.1038/srep32150
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of phonon-defect interactions: phonon scattering vs. phonon trapping

Abstract: The interactions between thermal phonons and defects are conventionally described as scattering processes, an idea proposed almost a century ago. In this contribution, ab-initio molecular-dynamics simulations provide atomic-level insight into the nature of these interactions. The defect is the Si|X interface in a nanowire containing a δ-layer (X is C or Ge). The phonon-defect interactions are temperature dependent and involve the trapping of phonons for meaningful lengths of time in defect-related, localized, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 56 publications
(76 reference statements)
1
24
0
Order By: Relevance
“…Shear displacements are known to be strongly damped by defects and boundaries. 35 The intensity evolution of the 130 spot from such defective samples is shown in Figure 4 . Two sample thicknesses are included, 0.06 IMFP (∼6 nm) and 0.21 IMFP (∼20 nm).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shear displacements are known to be strongly damped by defects and boundaries. 35 The intensity evolution of the 130 spot from such defective samples is shown in Figure 4 . Two sample thicknesses are included, 0.06 IMFP (∼6 nm) and 0.21 IMFP (∼20 nm).…”
Section: Resultsmentioning
confidence: 99%
“…TEM observations show that nonuniform samples that host defects often do not exhibit a strong shear phonon response in the temporal traces (TEM image in Supporting Information Figure S5). Shear displacements are known to be strongly damped by defects and boundaries . The intensity evolution of the 130 spot from such defective samples is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The thermal conductivity of a material must be high to keep a low thermal budget in a nanoscale device [3], for instance, while it should be as low as possible when it comes to the engineering of an efficient thermoelectric [4,5]. The thermal conductivity can be tuned to some extent by nanostructuring, adding defects [6,7], or designing periodic superstructures [8,9], but it would be desirable to be able to dynamically modify it. Besides an increased flexibility in materials design, this would also open the way to heat-based signal processing and computing [10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite lack of good methods to directly identify locons within tapered bottlebrush polymers, we previously demonstrated that even BB-2 has significantly more locons than PNb (backbone) in frequency ranges of 50−90 THz due to the existence of side chains, as shown in participation ratio plots of Figure 3d in ref 40. Locons do not significantly contribute to thermal conductivity, 52 could trap energy, 53 and become the bottleneck for heat conduction. Localization asymmetry can thus contribute to the spatial dependence of thermal conductivity.…”
mentioning
confidence: 99%